1994
DOI: 10.1152/ajpcell.1994.267.2.c402
|View full text |Cite
|
Sign up to set email alerts
|

Interferon-gamma induces a cell surface phenotype switch on T84 intestinal epithelial cells

Abstract: Intestinal epithelia are in intimate contact with submucosal and intraepithelial lymphocytes. The concentration of intraepithelial lymphocytes increases during inflammatory processes, and, when stimulated, these cells generate cytokines such as interferon-gamma (IFN-gamma). In this study, we examined the effect of recombinant human IFN-gamma on ion transport events in T84 cells, a crypt epithelial cell line widely used to study electrogenic Cl- secretion, the transport event responsible for mucosal hydration. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
77
1
1

Year Published

1997
1997
2012
2012

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(86 citation statements)
references
References 17 publications
7
77
1
1
Order By: Relevance
“…Thus the upregulation of CFTR, as shown in our series of inflamed tissues, might result in both increased secretion of Cl Ϫ and decreased absorption of sodium of the mucosa and ultimately contribute to diarrhea. Previous studies with intestinal epithelial cells have produced contradictory results, because one group reported a decrease in CFTR expression, and others have observed that CFTR expression is unchanged (6,11,32). In our study, the expression of the CFTR protein was detected both in healthy and inflamed colon mucosa by immunohistochemistry, although the overall expression level of CFTR in colon is not abundant.…”
Section: Discussioncontrasting
confidence: 72%
See 1 more Smart Citation
“…Thus the upregulation of CFTR, as shown in our series of inflamed tissues, might result in both increased secretion of Cl Ϫ and decreased absorption of sodium of the mucosa and ultimately contribute to diarrhea. Previous studies with intestinal epithelial cells have produced contradictory results, because one group reported a decrease in CFTR expression, and others have observed that CFTR expression is unchanged (6,11,32). In our study, the expression of the CFTR protein was detected both in healthy and inflamed colon mucosa by immunohistochemistry, although the overall expression level of CFTR in colon is not abundant.…”
Section: Discussioncontrasting
confidence: 72%
“…Because there was no significant change in the levels of SLC26A3 and SLC9A3 transporters even in severe colitis, it is tempting to speculate that a similar model of inhibition of NaCl absorption might exist in human colon too. However, several different studies using different conditions or models have produced ambiguous results regarding the regulation of the expression of different apical and basolateral transporters (6,11,32,38,52). Significant differences may occur in different models, and there may be differences even between UC and other types of intestinal inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Gastric MNC cells have been shown to produce predominantly IFN␥ (39), which has numerous deleterious effects on local inflammation and epithelial barrier function (53,54). Together, these findings support the notion that gastric epithelial cells may contribute to their own destruction as a consequence of their ability to activate potentially deleterious helper T cell responses.…”
Section: Discussionmentioning
confidence: 73%
“…The intestinal epithelial cell line T84 forms polarized monolayers in vitro and has been used extensively as a model to investigate a variety of physiologic and immunologic properties of the intestinal epithelium (e.g., 1,18,24). To study the HLA class II antigen processing pathway in a manner independent of the cytokines required to induce class II expression in this cell line, we used retroviral-mediated gene transfer to generate T84 cells that constitutively express surface HLA-DR molecules, and demonstrated that these cells could both process and present antigen to CD4 ϩ T lymphocytes (14).…”
Section: Resultsmentioning
confidence: 99%